Failure of bortezomib to cure acute antibody‐mediated rejection in a non‐compliant renal transplant patient. (9th July 2013) - Ryckewaert, A.; Allain‐Launay, E.; Moreau, A.; Blancho, G.; Cesbron, A.; Blin, N.; Roussey, G.
Abstract: Bortezomib has appeared recently as a potential active treatment for acute AMR for few years. We reported a patient who received two courses of bortezomib for the treatment of an acute AMR associated with de novo HLA DSA that occurred 18 months after renal transplantation because of non‐compliance. Graft biopsy revealed features of acute humoral rejection with plasmocyte infiltration and C4d staining. Bortezomib was associated with corticosteroid pulses, IVIgs, and PP. Despite this rapid management, the patient lost his graft and carried on dialysis. Bortezomib therapy in addition to current therapy of AMR is not always effective in the treatment for late acute AMR in renal transplantation. We discuss on the place of such a treatment and other therapeutic strategies in this indication.